Thai Language learning Management Model for Chinese Students in Private Higher Education institutions in Bangkok - Lu, Xuelian; Kawmongkon, Songyos; Dechhome, Patchara (Arts of Management Journal, 2024)
This research aimed to study the Thai language learning management model for Chinese students studying in private higher education institutions in Bangkok. The research procedure was divided into three steps. Step 1: Study the administrative conditions of Thai language learning for Chinese students studying in private higher education institutions in Bangkok. Data were collected from 208 respondents and in-depth interviews with six key informants. The research instruments were a set of semi-structured interview forms and questionnaires. The statistics used for data analysis were percentages, mean, and standard deviation. Step 2: Create a Thai language learning management model for Chinese students studying at private higher education institutions in Bangkok. Data were collected from 208 respondents, and the draft model evaluated with 10 key informants. The research instruments were a set of questionnaires and a sketch assessment form. The statistics used for data analysis were exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and Chi-square. Step 3: Evaluate the feasibility and utility of the administration model by experimenters in Thai language learning for Chinese students studying at private higher education institutions in Bangkok. Selected by purposive sampling from 20 respondents. The research instrument was a set of evaluation forms. The statistics used for data analysis were chi-squares. The research found that the Thai language learning management model for Chinese students studying in private higher education institutions in Bangkok consists of six main components: 1) Good teachers; 2) Teaching methods; 3) Teaching media; 4) Measurement and evaluation; 5) Student success; and 6) Thai language learning management processes for Chinese students consist of four steps: planning, organizing, controlling, and acting. The results of the model evaluation in terms of accuracy, propriety, feasibility, and utility overall subcomponents and indicators were consistent (p-value >.05).